PENINGKATAN PERKEMBANGAN KOGNITIF MELALUI SENSORY PLAY PADA ANAK USIA 4-5 TAHUN DI SPS KEMUNING 26 MUMBULSARI TAHUN AJARAN 2025-2026 - Eka Husseina, Ikrimah; M. Fadil Djamali; Muhammad Agus Sugiarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The goal of this research is to use sensory play at SPS Kemuning 26 to enhance the cognitive development of children between the ages of four and five. The issue addressed in this study is the low level of children's cognitive development achievement, especially in the ability to group, understand cause-effect relationships, and solve simple problems, which is thought to be influenced by the less than optimal learning strategies based on direct experience. The Classroom Action Research (CAR) design used in this study was conducted in two cycles, each of which included stages for planning, action, observation, and reflection. This study involved four to five-year-old students at SPS Kemuning 26. Structured observation, documentation, and evaluation of children's development were utilized to collect data, and quantitative and qualitative descriptive approaches were employed for data analysis. Developmental completeness criteria were used to identify success indicators. The findings of the study indicated an improvement in children’s cognitive development achievements in each cycle after the implementation of sensory play, which was marked by an increase in the percentage of children's developmental completeness according to the established indicators. These results suggest that early childhood cognitive development can be stimulated by sensory play as a learning approach. Therefore, sensory play is suggested as an innovative, experience-based approach to learning in early childhood education.